2020
DOI: 10.3390/ani10081246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Source of Zinc on the Tissue Accumulation of Zinc and Jejunal Mucosal Zinc Transporter Expression in Holstein Dairy Calves

Abstract: Zinc is considered to be an anti-diarrheal agent, and it may therefore reduce the incidence of diarrhea in young calves. In the present study, we aimed to compare the effect of zinc source on growth performance, the incidence of diarrhea, tissue zinc accumulation, the expression of zinc transporters, and the serum concentrations of zinc-dependent proteins in neonatal Holstein dairy calves. Eighteen male newborn Holstein dairy calves were fed milk and starter diet supplemented with or without 80 mg zinc/d in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(49 reference statements)
2
8
0
Order By: Relevance
“…Oxidative stress happens when the excessive production of reactive oxygen species overwhelms the capacity of antioxidant systems in the body (27,28). Previous studies have shown that zinc has an antioxidant function (29), and supplementation with ZM reportedly decreases the concentration of MDA, but increases that of MT and T-AOC in the serum of ruminants (14,17,23), and similar results were also observed in the present study. Different from ZM, ZP did not present the same antioxidant effects as ZM because it did not affect the serum MT or T-AOC concentrations compared with the CON group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Oxidative stress happens when the excessive production of reactive oxygen species overwhelms the capacity of antioxidant systems in the body (27,28). Previous studies have shown that zinc has an antioxidant function (29), and supplementation with ZM reportedly decreases the concentration of MDA, but increases that of MT and T-AOC in the serum of ruminants (14,17,23), and similar results were also observed in the present study. Different from ZM, ZP did not present the same antioxidant effects as ZM because it did not affect the serum MT or T-AOC concentrations compared with the CON group.…”
Section: Discussionsupporting
confidence: 91%
“…The NDF and ADF contents were analyzed by the methods described by Van Soest et al (21). The zinc concentration in the milk and starter were determined by inductively-coupled plasma optical emission spectroscopy (ICP-OES), as described in the Chinese National Standards (GB 5009.268, China, 2016) with some modifications (14).…”
Section: Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended dosage of therapeutic zinc for the treatment of acute diarrhea is 20 mg per day for above six and 10 mg per day for under six months of children until 10–14 days were prescribed [ 1 ]. The low level of zinc in serum is estimated to be responsible for 21% of worldwide deaths for under-five age children [ 7 ]. Particularly, it can demote the number and functioning of neutrophils and natural killer cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A newly available amino acid chelate is bis-glycinate bound Zn (Plexomin Zn, Phytobiotics, Eltville, Germany), which consists of two equivalents of glycine bound to one equivalent of Zn. Organic Zn sources have been shown to be more bioavailable than inorganic Zn sources when supplemented to ruminants ( Wright and Spears, 2004 ; Pal et al, 2010 ; Ma et al, 2020 ), but little research has been conducted utilizing bis-glycinate bound Zn. Unlike other trace minerals, such as Cu, tissue concentrations of Zn do not readily change in response to dietary supplementation.…”
Section: Introductionmentioning
confidence: 99%